Sarcopenia in rheumatoid arthritis: Is it a common manifestation?. (26th September 2020) - Tekgoz, Emre; Colak, Seda; Ozalp Ates, Funda Seher; Sonaeren, Ilknur; Yilmaz, Sedat; Cinar, Muhammet
Abstract: Objective: To evaluate the presence of sarcopenia in patients with rheumatoid arthritis (RA). Method: This cross‐sectional study included 100 patients with RA and 100 gender‐matched healthy individuals. Sarcopenia was assessed by performing tests evaluating muscle strength, muscle mass, and physical performance, using the criteria determined by The European Working Group on Sarcopenia. Sarcopenia is defined as a decrease in muscle strength and muscle mass. On the other hand, presarcopenia is defined as a decrease in muscle strength with a normal muscle mass. Results: The participants comprised of 70 females and 30 males. The frequency of presarcopenia was 35% in the RA group and 9% in the control group ( P < .001). Results of handgrip and gait speed tests were lower in the RA group than in the healthy control group ( P = .002 and P < .001, respectively). Presarcopenia was seen at higher rates among female and older patients, and patients with longer disease duration. Disease activity scores were higher in patients with presarcopenia than in patients without sarcopenia ( P < .05). In multivariate regression analysis for presarcopenia; a statistically significant association was found between handgrip test results and age, gender, and disease activity ( P < .001, R 2 = .62). Conclusions: Longer disease duration and higher disease activity may provoke the development of sarcopenia due to chronic inflammation in patients with RA. Physicians should be aware of the development of sarcopenia during the course of disease and take into account the preservative and preventive methods against sarcopenia by encouraging them about exercise along with controlling disease activity.